The manufacturing of caustic soda by electrolytic process - Mayuyu, Renato (College of Engineering, 1961)
This plant design for the manufacture of Caustic soda by electrolysis is designed with a capacity of 50 tons per day of 50% caustic. The Plant requires a fixed capital investment of 9,250,644.00 and curtails a total cost of 11,150,644.00. The market survey conducted shows many prospective use of the product as well as the by-products. However, due to the highly competitive situation existing among the local producers and also due to the fact that raw materials supply is not consistent, the erection of this plant is not recommended.